Development And Validation Of The Bilingual (english-malay) Version Of Knowledge On Calcium Supplement-12 (knowcas-12) Questionnaire - Hizlinda Tohid; Fathima Begum Syed Mohideen; Aida Jaffar; Tan Chai Eng; Naemah Sariffudin; Noor Azimah Muhammad (Malaysian Public Health Physicians' Association, 2024)
To date, specific questionnaire assessing knowledge on calcium supplement is unavailable. Thus, we aimed to develop and validate this questionnaire. Four areas of knowledge (calcium in general, dietary calcium, benefits and risk of calcium supplement, and practices that reduce its benefits) were identified through literature review and interviews with ten doctors. Twelve items were created in English and reviewed by two family medicine specialists, an orthopaedic surgeon, and a pharmacist. A bilingual (English-Malay) questionnaire was produced via back-to-back translation and face validity was tested on seven patients. Discriminative validation was done by comparing knowledge scores between patients, medical students and doctors. Test-retest reliability was tested with a two weeks interval. Subsequently, the questionnaire was piloted on 100 patients. The KnowCaS-12 scores of doctors were significantly higher than those of patients (p<0.001) and students (p<0.001), indicating good discriminative validity. Although the Cronbach’s alpha was 0.68, it had good test-retest reliability [Spearman’s rho correlation: 0.40, p=0.02; pre- and post-test score median (IQR): 8.00 (3.00) and 9.00 (2.00) respectively, p-value of Wilcoxon Signed Ranks test: 0.08). The pilot study showed 52.5% of the participants took calcium supplement. Their median (IQR) for KnowCaS-12 was 7.00 (6.00), which was not significantly different from those who did not take calcium supplement. In conclusion, the bilingual KnowCaS-12 questionnaire appears to have good content validity, face validity, discriminative validity and test-retest reliability, thus it can be used for future studies. Practice of consuming calcium supplement seems to be common and users’ knowledge regarding calcium supplement was only moderate.